The sexual education of Edith Wharton - Erlich, Gloria C. (University of California Press, 1992)
Starting with the tensions in the early family constellation, Gloria C. Erlich traces Edith Wharton's erotic evolution--from her early repression of sexuality and her celibate marriage to her discovery of passion in a rapturous midlife love affair with the bisexual Morton Fullerton. Analyzing the novelist's life, letters, and fiction, Erlich reveals several interrelated identity systems--the filial, the sexual, and the creative--that evolved together over the.